Density Based Breast Segmentation For Mammograms Using Graph Cut Techniques. - Saidin, Nafiza; Ngah, Umi Kalthum; Mat Sakim, Harsa Amylia; Siong, Ding Nik; Mok, Kim Hoe (2009)

(untitled)
In this work we explore the application of graph cuts techniques to the problem of finding the boundary of different breast tissue regions in mammograms.